Agrobacterium tumefaciens-mediated genetic transformation of Chlorella sorokiniana - Gómez-Espinoza, Olman (2018)
Microalgae have become a viable platform for several biotechnological applications such as the production of biofuel, vitamins, carotenoids, enzymes, pharmaceuticals and recombinant proteins. Within this group, Chlorella sorokiniana have the requirements to become an industrial microorganism due to its ability to supports considerable fluctuations in temperature, pH and salinity. In this work, C. sorokiniana was used to determine optimum transformation conditions using Agrobacterium tumefaciens. It has been determined that bacterial density of OD600 = 1.5, 3 days of co-cultivation at 24°C in pH 5.6, 150 mM acetosyringone and two days post co-cultivation recovery period are the optimum conditions for C. sorokiniana transformation.